2014 IEEE International Advance Computing Conference (IACC) 2014
DOI: 10.1109/iadcc.2014.6779387
|View full text |Cite
|
Sign up to set email alerts
|

ReP-ETD: A Repetitive Preprocessing technique for Embedded Text Detection from images in spam emails

Abstract: Abstract-Email

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Authors in [344] applied various pattern recognition and computer vision techniques to detect image-based spam. Further similar studies can be found in [345][346][347][348][349].…”
Section: And Spam On Twittersupporting
confidence: 64%
“…Authors in [344] applied various pattern recognition and computer vision techniques to detect image-based spam. Further similar studies can be found in [345][346][347][348][349].…”
Section: And Spam On Twittersupporting
confidence: 64%
“…Text-based 9 [18], [19], [20], [21], [22], [23], [24], [25], [26] Image-based 16 [27], [28], [29], [9], [30], [31], [32], [33], [34], [35], [17], [5], [36], [37], [38], [39] [20], [30], [34], [5], [37], [38], [39] Dredze 10 5789 spam (spam =3239 & ham = 2550) [30], [31], [33], [34], [40], [17], [5], [37], [28], [21] Enron corpus 1 Not specified [22] SMS spam 1 Not specified [18] Princeton spam corpus [20], [24], [30], [31], [41], [32],…”
Section: No Of Studies Referencementioning
confidence: 99%
“…The proposed classifier cannot detect image spam email. The same OCR tool was used in the work of some researchers [21], [22], [24], [23]. They examined and applied OCR software to filter image spam email.…”
Section: Spam Classification Techniques Analysis and Reviewmentioning
confidence: 99%